La salud mental del Trabajo Social en Cataluña - UREÑA HIDALGO, Agustina (Cuadernos de Trabajo Social, 2010)
The article places the field of Mental Health in context, beginning with European welfare policies and how these take shape within Spain. It analyzes the model of mental health in Catalonia and how it is being implemented. The second part of the article centers on identifying what aspects are affecting Social Work in the field of Mental Health and what role said professionals play in the new care model.